2018
DOI: 10.1371/journal.pone.0199365
|View full text |Cite
|
Sign up to set email alerts
|

Age-adjusted Charlson Comorbidity Index as a prognostic factor for radical prostatectomy outcomes of very high-risk prostate cancer patients

Abstract: PurposeProstate cancer (PC) is a devastating and heterogeneous condition with diverse treatment options. When selecting treatments for patients with very high-risk PC, clinicians must consider patient comorbidities. We investigated the efficacy of the age-adjusted Charlson Comorbidity Index (ACCI) as a prognostic factor for patient outcomes after radical prostatectomy (RP).Materials and methodsWe retrospectively investigated the medical records of PC patients at our institution who underwent RP from 1992 to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Like our results there was a high negative predictive value for adverse events (21). Another study in patients undergoing prostatectomy MCI was an effective prognostic factor (22). A study in kidney transplant recipients suggested MCI in clinical practice to stratify the mortality hazard in patients who undergo renal transplantation (23).However another study showed no association between MCI and mortality (24) In decision we demonstrated that MCI combined with procalcitonin and CRP can be used reliably for predicting mortality instead of APACHE II in medical ICU cases.…”
Section: Discussionsupporting
confidence: 83%
“…Like our results there was a high negative predictive value for adverse events (21). Another study in patients undergoing prostatectomy MCI was an effective prognostic factor (22). A study in kidney transplant recipients suggested MCI in clinical practice to stratify the mortality hazard in patients who undergo renal transplantation (23).However another study showed no association between MCI and mortality (24) In decision we demonstrated that MCI combined with procalcitonin and CRP can be used reliably for predicting mortality instead of APACHE II in medical ICU cases.…”
Section: Discussionsupporting
confidence: 83%
“…Several studies reported the clinical impact of ACCI on survival in patients with various cancers including those who underwent surgical resection 13–16 . Here, we demonstrated that ACCI was significantly prognostic for OS, but not for PFS in BTC patients receiving palliative chemotherapy.…”
Section: Discussionmentioning
confidence: 58%
“…While comorbidities increase with age, chronological age alone would not reflect overall physical status in those patients because variations among each individual tend to be large in elderly patients. Recently, the age‐adjusted Charlson comorbidity index (ACCI) has been widely used in the field of clinical oncology, 12 demonstrating a prognostic value in several types of cancer 13–16 . Herein, we aimed to clarify the impact of age and comorbidity assessment indicated by ACCI on clinical outcomes in patients with advanced or recurrent BTC undergoing palliative chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The CCI has been used to measure comorbidity and adjust for associated risks in survival models based on the various data sources, including clinical trials, prospective and retrospective cohort studies, and claims data [ 26 33 ]. Recently, population-based health care claims data have been used more frequently in studies of health-related outcomes, as these data could yield generalizable results.…”
Section: Discussionmentioning
confidence: 99%